26.032000

How do you find g(-3) if g(x) = x³ + 3x - 5?

mrsdarcy1981 Mathematics 2 4

How do you find g(-3) if g(x) = x³ + 3x - 5?

Posted by mrsdarcy1981 | Posted at Mar 26, 2000 | Categories: Mathematics

Answers

yassautumn
yassautumn

[latex]g(-3)=(-3)^3+3cdot(-3)-5 g(-3)=-27-9-5 g(-3)=-41[/latex]

Mar 26, 2000 01:21
TamaraTewksbury170
TamaraTewksbury170

To resolve the matter of changing x into (- 3) ​​in equation : [latex]g(x) = x^{3} + 3x - 5[/latex] [latex]g(-3) = (-3)^{3} + 3(-3) - 5[/latex] [latex]g(-3) = -27 + (-9) - 5[/latex] [latex]g(-3) = -27 -9 - 5[/latex] [latex]oxed{g(-3) = -41}[/latex]

Mar 26, 2000 01:25

Leave a answer